x2-6x+9=100

Move 100 to the left side of the equation by subtracting it from both sides.

x2-6x+9-100=0

Subtract 100 from 9.

x2-6x-91=0

Consider the form x2+bx+c. Find a pair of integers whose product is c and whose sum is b. In this case, whose product is -91 and whose sum is -6.

-13,7

Write the factored form using these integers.

(x-13)(x+7)=0

(x-13)(x+7)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

x-13=0

x+7=0

Set the first factor equal to 0.

x-13=0

Add 13 to both sides of the equation.

x=13

x=13

Set the next factor equal to 0.

x+7=0

Subtract 7 from both sides of the equation.

x=-7

x=-7

The final solution is all the values that make (x-13)(x+7)=0 true.

x=13,-7

Solve Using the Square Root Property x^2-6x+9=100